Seleção de genitores de algodoeiro colorido visando qualidade de fibra e potencial produtivo - Medeiros, Luiza Amaral (2021)
Cotton (Gossypium hirsutum L) is the main natural textile fiber in the world. Although its worldwide production is mainly composed of white fiber cultivars, naturally colored cotton has also conquered the international textile market, presenting a market potential for cotton farmers. However, its viability for large-scale production is compromised by factors such as: lower fiber yield and quality compared to white fiber cultivars available on the market. Therefore, the objective of the work was to evaluate the combinatorial capacity of cotton accessions through the methodology of partial diallel analysis for the development of colored cotton lines with fiber quality and superior productive potential. The work was carried out under field conditions in Uberlândia-MG in the 2019/2020 harvest. The experiment was carried out in a randomized block design with three replications and 34 treatments (10 white and colored fiber cotton parents DP1552, BRS433, FM 980, TMG 47, TMG 82, FMT 705, BRS Topázio, BRS Rubi, PROMALG Red and PROMALG Okra) and 24 hybrid combinations. 12 Morpho-agronomic evaluations were carried out in addition to the evaluations of yield and technological fiber characteristics. Analysis of variance, diallel analysis using the Griffing methodology and grouping test by Scott-Knott were performed. There was a predominance of additive genetic effects in the control of the expression of the technological characteristics of the fiber. The hybrid combinations PROMALG Red x BRS433 and BRS Rubi x DP1552 are recommended to promote increases in the productivity of colored fiber genotypes. PROMALG Red x TMG82 showed the best complementarity between the parents, being promising for obtaining progenies with superior colored fiber quality. The BRS Rubi x FMT705, PROMALG Red x TMG82 and PROMALG Okra x DP1552 combinations ar recomended for the development of progenies with a focus on longer fiber length (UHML).